Investigating the effectiveness of fluid viscous damper in reducing the effect of seismic sequence on steel bending frame designed on type c soil (Journal of Civil Engineering Researchers, 2023)
Aftershocks can always cause the collapse of structures damaged by the main earthquake. In this article, the seismic performance of an 8-story steel bending frame designed in c-type soil was first subjected to the seismic sequence of an earthquake and an aftershock, and then the same building with the addition of a fluid viscous damper (Fluid Viscous Damper) was evaluated. The results showed that the seismic performance of the studied frame under the effect of severe aftershocks with the presence of a liquid viscous damper is very different from the case without FVD. For example, the maximum displacement of the structural floors was reduced by 60% compared to the case without a damper. It was also found that while most of the aftershocks in buildings without dampers cause a significant increase in the permanent displacement of the roof, in the presence of dampers, this amount has decreased significantly, although in general, the damage caused by the effect of aftershocks on the building is much more az It will be from a state in which the structure is only subjected to the main earthquake
Keywords: Aftershock; Mainshock; Seismic sequence; Steel moment frame; Fluid Viscous Damper